2019
DOI: 10.1002/ange.201904890
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Pyrrole Reactivity upon Confinement within a Cyclodextrin Metal–Organic Framework

Abstract: Metal–organic frameworks can be used as porous templates to exert control over polymerization reactions. Shown here are the possibilities offered by these crystalline, porous nanoreactors to capture highly‐reactive intermediates for a better understanding of the mechanism of polymerization reactions. By using a cyclodextrin framework the polymerization of pyrrole is restricted, capturing the formation of terpyrrole cationic intermediates. Single‐crystal X‐ray diffraction is used to provide definite information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Previous works on the oxidative polymerization of pyrrole and EDOT reported that the conductivity of the host–polymer complexes ranges from 10 –1 to 10 –7 S cm –1 depending on the morphology and properties of the host (MOFs, PCPs, etc.). The conductivity of the 1· PPy and 1· PEDOT complexes lies closer to the single crystals of the terpyrrole cationic polymers confined in the cyclodextrin MOFs . Considering that morphological defects (crack or bend) of the single crystals of 1· PPy and 1· PEDOT will tend to lower their conductance, the conductivity values observed here may represent a lower bound on what is achievable.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous works on the oxidative polymerization of pyrrole and EDOT reported that the conductivity of the host–polymer complexes ranges from 10 –1 to 10 –7 S cm –1 depending on the morphology and properties of the host (MOFs, PCPs, etc.). The conductivity of the 1· PPy and 1· PEDOT complexes lies closer to the single crystals of the terpyrrole cationic polymers confined in the cyclodextrin MOFs . Considering that morphological defects (crack or bend) of the single crystals of 1· PPy and 1· PEDOT will tend to lower their conductance, the conductivity values observed here may represent a lower bound on what is achievable.…”
Section: Resultsmentioning
confidence: 58%
“…PPy is a simple and well-studied example, which undergoes polymerization through radical cationic intermediates . The rapid rate of the reaction affords primarily α-α′ connections as well as other C–C couplings, which lead to crosslinking that can modulate the conductivity of the resulting polymer. , The polymerization of pyrrole has been studied in numerous confined spaces including in zeolites, AAOs, MOFs, , and in coordination nanochannels . Similarly, PEDOT has been synthesized in the pores of porous coordination polymers, , nanochannels, , SURMOFs, and on nanoporous layer glass to increase the conductivity of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…This cavity is crucial for the various encapsulation purposes of CD-MOFs. 99 Additionally, CD-MOF-1 has triangular channels of 0.4 nm size that can be observed upon orientation of the crystal structure at 45° with respect to the crystallographic axes (Fig. 4b).…”
Section: Synthesis Structure and Properties Of Cd-mof Materialsmentioning
confidence: 97%
“…This cavity is crucial for the various encapsulation purposes of CD-MOFs. 99 Additionally, CD-MOF-1 has triangular channels of Reproduced with permission. 102 Copyright 2017, American Chemical Society.…”
Section: Cd-mofsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) 1 3 have become a hot topic of research during the past decades due to the concomitant presence of atheistically pleasant porous high-dimensional structures with intriguing net topologies and thrilling chemical and physical properties. Indeed, these hybrid materials—consisting of metal ions (or small metal clusters) linked by a wide diversity of organic spacers—have been able to make themselves a functional entity by controlling the assembling of their subunits, which have enabled them to find applications in gas storage and separation, 4 6 drug delivery, 7 9 molecular recognition, 10 − , 14 and catalysis 15 18 as well as in templating the in situ growth/encapsulation of a wide variety of functional moieties 19 , 20 …”
Section: Introductionmentioning
confidence: 99%